2017
DOI: 10.3390/md15080254
|View full text |Cite
|
Sign up to set email alerts
|

Does Osmotic Stress Affect Natural Product Expression in Fungi?

Abstract: The discovery of new natural products from fungi isolated from the marine environment has increased dramatically over the last few decades, leading to the identification of over 1000 new metabolites. However, most of the reported marine-derived species appear to be terrestrial in origin yet at the same time, facultatively halo- or osmotolerant. An unanswered question regarding the apparent chemical productivity of marine-derived fungi is whether the common practice of fermenting strains in seawater contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Our results illustrate medium-dependent changes of bioactivity. This has also previously been shown by Overy et al ( 2017 ) in a comprehensive study where the same ex-type strain of Aspergillus aculeatus , a halotolerant terrestrial fungus, produced distinct culture media-specific metabolites when grown with different osmotic pressures as well as laboratory (site) specific metabolites.…”
Section: Discussionsupporting
confidence: 76%
“…Our results illustrate medium-dependent changes of bioactivity. This has also previously been shown by Overy et al ( 2017 ) in a comprehensive study where the same ex-type strain of Aspergillus aculeatus , a halotolerant terrestrial fungus, produced distinct culture media-specific metabolites when grown with different osmotic pressures as well as laboratory (site) specific metabolites.…”
Section: Discussionsupporting
confidence: 76%
“…It can be argued that “marine-derived” fungi are a proven source of new natural products; this is not in dispute as over a thousand new compounds or new derivatives of known molecules have been discovered over the past few decades. However, recent evidence has demonstrated that the new chemistry is a result of saline stress, where terrestrial counterparts of the same species produce the same chemistry as discovered from marine-derived strains when grown on media containing seawater [70]. Simply mining the terrestrial isolates of osmotolerant species on media containing seawater will achieve the same ends.…”
Section: Discussionmentioning
confidence: 99%
“…Overy and colleagues investigated the effects of osmolarity and salinity on the production of SMs in the terrestrial halophilic fungus, Aspergillus aculeatus [ 86 ]. They found that SMs such as aspergillusol, secalonic acid D, aculene C and another aculene analog were up-regulated in the fungus under saline conditions; with production of aspergillusol in particular being associated with a halotolerant response to saline conditions involving seawater/sea salts.…”
Section: Change In Physical Parametersmentioning
confidence: 99%